Reducing caesarean section rates in Robson groups 1 and 3: a quality improvement initiative in a private Brazilian hospital - Ana Pilar Betran; Maria Regina Torloni; Mario Macoto Kondo; Vera Denise de Toledo Leme; Daniela Cristina da Silva Carvalho; Lissandra Borba da Cunha; Elaine Galvão; Andreia Fratoni Ledo; Monica M Siaulys (BMJ Open Quality)
Private Brazilian hospitals have one of the highest caesarean section (CS) rates in the world. Caesareans may have short- and long-term implications for the health of mothers and babies. The primary objective of this project was to assess the effects of an intrapartum quality improvement (QI) initiative on CS rates and on maternal/perinatal outcomes. A bundle targeted at internal healthcare providers (HCP) on-duty in the labour and delivery (LD) ward of a private Brazilian hospital was created in 2020 (first period) and implemented in 2021–2022 (second period). External HCPs managing their own private patients served as a control group. The bundle focused on improving intrapartum care in women without previous CS in spontaneous labour with single cephalic pregnancies at term (Robson groups 1 and 3). The bundle included a collaborative midwifery–obstetrician intrapartum model of care, a new LD ward medical coordinator, daily supportive supervision, updated LD guidelines and internal HCP refresher training on teamwork and intrapartum care. We analysed changes in outcomes between the two periods and the two HCP teams. The analyses included data on 24 414 women who gave birth (≥500 g) over a 30-month period.Among women managed by internal HCPs, there was a 32% relative decrease in Robson-1 CS rates (65.7% vs 44.6%, first vs second period, relative rate ratio (RRR)=0.68, p<0.0001), a 43% relative decrease in Robson-3 CS rates (25.4% vs 14.5%, RRR=0.57, p=0.007) and an 11% relative decrease in the overall CS rates (82.7% vs 73.8%, RRR=0.89, p<0.0001). There were no significant changes in adverse maternal and perinatal outcomes nor in maternal satisfaction (primary outcomes), in Robson-1 and 3 groups managed by internal HCPs.In summary, an intrapartum care QI initiative was associated with a safe reduction of CS rates in Robson-1 and 3 women managed by on-duty HCPs in a private Brazilian hospital.